Representation model and cloud-based orchestrator for pervasive storytelling - Almeida, Pedro H. V.; Pernisa Jr, Carlos; Moreno, Marcelo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2022)
Internet of Things (IoT) devices are increasingly accessible and are part of people’s daily lives. This opens up great possibilities for innovative storytelling experiences, allowing new forms of consumption, going beyond conventional multimedia. In this context, the need for advances in the representation and orchestration of pervasive storytelling is perceptible. This work proposes a conceptual model called Pervasive Storytelling (PST) that aims to represent stories to be told in a pervasive way. By modeling the specific domain of pervasive storytelling at a high level of abstraction, the model supports the variability typical of pervasive environments, such as changes in location, device connectivity, proximity between users, and others. This work also proposes a cloud presentation engine, capable of interpreting and orchestrating storytelling instances represented through PST.